Clinical development of neridronate: potential for new applications - Gatti D; Rossini M; Viapiana O; Idolazzi L; Adami S (Dove Medical Press, 2013)
Davide Gatti, Maurizio Rossini, Ombretta Viapiana, Luca Idolazzi, Silvano AdamiRheumatology Unit, Department of Medicine, University of Verona, Verona, ItalyAbstract: Neridronate is an aminobisphosphonate, licensed in Italy for the treatment of osteogenesis imperfecta (OI) and Paget's disease of bone (PDB). A characteristic property of neridronate is that it can be administered both intravenously and intramuscularly, providing a useful system for administration in homecare. In this review, we discuss the latest clinical results of neridronate administration in OI and PDB, as well as in osteoporosis and other conditions. We will focus in particular on the latest evidence of the effect of neridronate on treatment of complex regional pain syndrome type I.Keywords: bisphosphonates, osteogenesis imperfecta, osteoporosis, complex regional pain syndrome